2009
DOI: 10.1108/17504970910967573
|View full text |Cite
|
Sign up to set email alerts
|

Using digital technologies to address Aboriginal adolescents' education

Abstract: PurposeThe purpose of this paper is to examine how digital technologies were introduced in a collaborative literacy intervention to address a population long underserved by traditional schools: the Aboriginals of Canada.Design/methodology/approachSituated within a critical ethnographic project, this paper examines how digital technologies were introduced. The questions focused on: how can critical multiliteracies be used to engage students, in both academic and digital literacies development? In what ways does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Digital storytelling creates a context that provides students with control over their learning (Pirbhai-Illich 2010;Pirbhai-Illich et al 2009), and teaches them to make informed choice among resources (Ashman and Elkins 2009;Laycock and Stephenson 1993;Sprague and Pixley 2008). Whilst working on their videos, EFL/ESL students become engaged in the authentic decision-making process.…”
Section: Technology In Teaching Sciencementioning
confidence: 99%
“…Digital storytelling creates a context that provides students with control over their learning (Pirbhai-Illich 2010;Pirbhai-Illich et al 2009), and teaches them to make informed choice among resources (Ashman and Elkins 2009;Laycock and Stephenson 1993;Sprague and Pixley 2008). Whilst working on their videos, EFL/ESL students become engaged in the authentic decision-making process.…”
Section: Technology In Teaching Sciencementioning
confidence: 99%
“…Related to the two challenges discussed above, some teachers do not feel that they have sufficient knowledge to assess digital multimodal literacy. For instance, a participating high school classroom teacher, Joan (Pirbhai‐Illich, Turner, & Austin, ) reported that she felt she was not adequately prepared to design criteria to assess multimodal projects that she implemented in her class. In fact, some research points out the lack of teacher training in how to assess digital multimodal texts by students and suggests that teacher educators “provide training and support for integrating multimodality into an existing [teacher education] curriculum” (Choi & Yi, , p. 323) and ongoing professional development (Miller, ).…”
Section: Challenges Of Assessment For Digital Multimodal Literacymentioning
confidence: 99%
“…As a slightly different paper, collaborative action research (Pirbhai‐Illich, Turner, and Austin ) explored how multimodal literacy practices could be used to engage the Aboriginal adolescents in Canada in literacy development. In the process of the production of a video, these adolescents critically analyzed Aboriginal representations in the media and challenged how they were positioned in society.…”
Section: Disparate Possibilities Of Multimodal Literacy Practicesmentioning
confidence: 99%
“…More importantly, assessment criteria for print‐based academic literacy are not adequate for assessing the product of digitally and multimodally‐mediated texts (Wyatt‐Smith and Kimber ). This challenge was nicely illustrated by a research participant, a high school classroom teacher, Joan (Pirbhai‐Illich, Turner and Austin ). Because Joan did not have sufficient knowledge of criteria for multimodal projects and the end of the semester report card did not have space for reporting students' multimodal literacies, she ended up evaluating students' multimodal multimedia products by ‘using discrete skill‐based worksheets in order to complete her report cards’ (158).…”
Section: Challenges For Using Multimodal Literacies For Teaching and mentioning
confidence: 99%
See 1 more Smart Citation